Problematic sources : nineteenth-century investigations into Russian healing springs - Platonov, Evgenii (Array, 2021)
Traditional Russian worldviews explained healing from water sources in terms both Protestants and Catholics would have used elsewhere in Europe: as the grace of God or as the intervention of saints through associated relics or wonder-working icons. Holy wells were freely venerated within parishes until the eighteenth century when Peter the Great and the Holy Synod (the Russian Orthodox Church"s highest governing body) forbade pilgrimage to holy wells in a reformist drive to eradicate religious "superstitions." This essay employs primary sources to consider how nineteenth-century developments at Russian holy wells and mineral springs related to social class, economics and those eighteenth-century reforms that merged the church with government structures. While liturgical activities at holy wells and the designation of new holy wells was criminalized, mineral springs gained appeal for "scientific" cures and as resort enterprises for the upper classes.